Estimated cost-effectiveness and burden of disease associated with quadrivalent cell-based and egg-based influenza vaccines in Spain - Jesús Ruiz-Aragón; Ray Gani; Sergio Márquez; Piedad Alvarez (Human Vaccines & Immunotherapeutics, 2020)
Influenza is a viral respiratory disease that causes significant clinical and economic burden globally. Quadrivalent influenza vaccine (QIV) is frequently used to protect people who have a high-risk of developing influenza complications due to comorbidities. QIV offers protection against influenza A (A/H1N1 and H3N2) and B (B/Victoria, and B/Yamagata) strains. The European Medicines Agency has recently approved a cell-based QIV (QIVc) in people aged over 9 years old. QIVc has been shown to be more effective at preventing influenza than traditional egg-based QIV (QIVe). In this study, we use a health economic model adapted to Spain to assess the costs and outcomes associated with using QIVc instead of QIVe in people aged 9–64 at high-risk of complications. Observed vaccine coverage of 32% in the 9–17 age group, 17% in those aged 18–59, and 22% for ages 60–64 was used in the analysis. In total, 2.5 million people were vaccinated in the simulations. Using QIVc instead of QIVe was associated with 16,221fewer symptomatic cases, 4,522 fewer primary care visits, 1,015 fewer emergency room visits and 88 fewer hospitalizations. From a societal perspective, QIVc was more effective and less expensive compared to QIVe, leading to a cost-saving of €3.4 million. From a public payer perspective, the incremental cost-effectiveness ratio for QIVc vs QIVe was €12,852 per QALY gained. In conclusion, QIVc offers a cost-effective alternative to QIVe and should be considered as an alternative vaccine to QIVe for people aged 9–64 at high-risk of influenza complications in Spain.